Effect of pelvic organ prolapse reconstructive mesh surgery on the quality of life of Turkish patients: A prospective study - Gokmen Sukgen; Ünal Türkay (Wolters Kluwer Medknow Publications, 2020)
Objectives: The purpose of this study was to investigate transvaginal mesh treatment and its effect on the quality of life of Turkish patients with pelvic organ prolapse (POP). Turkish patients with POP were invited to participate in this study, and all the participants underwent prolapse surgery. Materials and Methods: The clinical outcomes, including effectiveness of the treatment and changes in the quality of life, were measured by the short form-36 survey. The data were analyzed using SPSS version 23. To analyze differences in the quality of life at the three aforementioned points in time, a paired sample t-test was used. Results: The results indicated that participants' quality of life increased after surgery. Some quality of life domains (i.e., vitality and mental health) as well as physical and mental health summary scores increased. Overall, transvaginal mesh treatment significantly improved the quality of life of Turkish patients with POP. Conclusion: Women who undergo transvaginal mesh treatment will have positive changes in the quality of life.